Taking Your iPhone to the Max - Sadun, Erica (Springer, 2017)
Taking Your iPhone to the Maxintroduces you to the iPhone, Apple’s handheld marvel of a device. Starting with a guide to setting up your iPhone and activating service, Taking Your iPhone to the Maxdocuments each of the iPhone’s built-in applications. You’ll discover how to connect to the Internet, send and receive e-mail, listen to your music, watch videos, and, of course, place phone calls. Filled with examples, how-to instructions, and complete feature coverage, this is the manual that should have shipped with your iPhone. It puts all the infor-mation you want to know into an easy-to-read reference.